Left Ventricular Papillary Fibroelastoma - Balboa, Cristina (2023)
Introduction: Cardiac papillary fibroelastoma is a rare benign primary cardiac tumor typically found on the valvular structures of the heart. Nonvalvular papillary fibroelastomas are exceedingly rare. We report the case of a 66-year-old male who presented with cerebellar infarctions and was found to have a mobile mass attached to the endocardial surface of the anteroseptal wall of the left ventricle. Cardiac magnetic resonance imaging demonstrated late gadolinium enhancement. Surgical excision of the cardiac mass was performed via the transaortic approach without intra-operative complications. Histopathologic examination confirmed the diagnosis of a papillary fibroelastoma. Some aspects related to the etiology, diagnosis and management of this entity are discussed.